Uwarunkowania przymrozków na przykładzie epizodu z lipca 1996 roku na Hali Izerskiej w Górach Izerskich w kontekście gospodarki leśnej - Urban, Grzegorz (Leśne Prace Badawcze, 2014)
This paper presents the characteristics of a frost period that occurred on July 20–23, 1996, in the center of the Izera Mountains in the context of forest management. The source data consisted of air temperature measurements from the author’s own work as well as data obtained from archival databases of the Institute of Meteorology and Water Management, Voivodeship Inspectorate of Environmental Protection, the University of Wrocław and the Bureau of Forest Management and Geodesy in Brzeg. Due to the unusual time of frost and its intensity, the impact of this particular period was extreme. For the center of the mountain dale Hala Izerska, the estimated probability of frost temperatures of -5.5°C two meters above ground level is 2.4% for the month of July. Therefore, in this area such a sharp decline of Tmin in the middle of the growing season is predicted to occur only once every 40–50 years. In the Izera Mountains, strong nocturnal decreases of Tmin below 0°C during the growing season occur almost every year causing significant damage to silviculture. Represented here by the mountain dale Hala Izerska, the central Izera Mountains are one of the coldest or even the coldest site in Poland in terms of absolute minimums of air temperature during the growing season. Knowledge on the impact of climate, such as thermal factors, on tree stands enables silvicultural work in mountain areas to be optimized, ultimately allowing funding to be rationalized. The distinct climatic conditions of mountain basins and valleys as well as slopes and plateaus of similar altitudes need to be taken into consideration.